Fitoremediasi Tanaman Rumput Benggala (Panicum Maximum Jacq) Terhadap Logam Kadmium (Cd) Sintetik dan Tanah TPA Tamangapa Antang Makassar - A. Reskianti Wardani; Syamsidar HS; Aisyah Aisyah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2013)
One way to reduce the pollution of soil is by using phytoremediation. In this study phytoremediation methods used to remediate the landfill Antang Makassar using wild plants Bengal grass (Panicum maximum Jacq) in metals accumulate Cd. Growing media used were pure land Antang landfill waste with the addition of a synthetic variation of Cd concentration of 2 ppm, 4 ppm, 6 ppm, 8 ppm and pure contaminated soil without the addition of synthetic waste. From the results obtained, the lower Cd concentrations of synthetic wastewater were added, the higher the absorption, the absorption maximum occurs on the addition of synthetic wastewater with concentration of 4 ppm Cd on day 7, is 0.0608 mg/Kg.